Worker Cooperatives in the United States, Redux. Issue 2 (20th May 2016) - Kennelly, James J.; Odekon, Mehmet
Abstract : Unfettered free market capitalism has adversely affected the socio‐economic well‐being of labor for over thirty years, leading to unprecedented income disparities in society. An alternative economic model that promotes worker ownership and economic democracy—the worker cooperative—is the focus of this study. Three exemplary case studies suggest that worker cooperatives are not only viable forms of businesses ‐ competitive and productive—but they are also democratic workplaces with participatory democracy guaranteeing individual and collective freedom, worker satisfaction, prosperity, and dignity. The essay concludes that self‐determination in the workplace that empowers labor is a transformative alternative strategy to successfully fight income inequality.